Scientific and technical studies on eco-efficient binary cements produced with thermally activated ichu grass: Behaviour and properties - Frias, Moises (2020)
The present research study analyses, for the first time, the viability of using thermally activated ichu grass as a supplementary cementitious material for the design of future eco-cements. To this end, the ichu ash resulting from the activation was characterised and its pozzolanic activity, the evolution of its mineralogical phases during the pozzolanic reaction and the physical-mechanical behaviour of the blended cementitious matrices were analysed. The results show that ichu ash exhibited high pozzolanic activity in a pure pozzolan/lime system as a consequence of its high reactive silica content. Conversely, its use in a pozzolan/cement system gave rise to negative effects due to the presence of important alkali contents in the ash (9.6% Na2O eq). The blended cements presented greater water demand, reduced capillary absorption, increased resistivity and lower mechanical properties (10-14%) as well as reduced average pore size than the reference mortar. These blended cement matrices comply with the physical-mechanical requirements established in the standards for the production of eco-cements.